The development and validation of mathematical reflective thinking test for prospective mathematics teachers using the Rasch model - Muntazhimah Muntazhimah; Reni Wahyuni (Jurnal Elemen, 2022)
Research on developing a mathematical reflective thinking test instrument for prospective mathematics teachers using the Rasch model is limited. This study aims to develop a reflective thinking ability test for prospective mathematics teachers using the Rasch model. The development steps consist of preparing a blueprint, writing items, reviewing items, conducting trials, analyzing test results, and revising. The test developed is a description test validated by five experts, consisting of two expert professors in evaluating mathematical ability, one expert lecturer in mathematical ability, and two expert lecturers in group theory. The test was also piloted on 26 students. The study's results using the Rasch model analysis showed that this instrument was "very reliable," and 12 of the 13 test items were "valid." The instrument has fulfilled all the stages of instrument development and was declared valid and reliable; thus, this test can be used to examine prospective mathematics teachers’ mathematical reflective thinking ability.